Space Charge Effect for Design Electron Gun Using Five Electrode Immersion Electrostatic Lenses - Hussein, Bushra H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Computer theoretical study has been carried out on the design of five electrode immersion electrostatic lens used in electron gun application. The finite element method (FEM) is used in the solution of the Poisson’s equation fro determine axial potential distribution, the electron trajectory under Zero magnification condition . The optical properties : focal length ,spherical and chromatic aberrations are calculated,From studying the properties of the designed electron gun. we have good futures for these electron gun where are abeam current 4*10-4A can be supplied by using cathode tip of radius 100 nm.